2015
DOI: 10.1099/vir.0.000202
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence and comparative virulence of raccoonpox virus: the first North American poxvirus sequence

Abstract: We report here the complete genome sequence of raccoonpox virus (RCNV), a naturally occurring North American poxvirus. This is the first such North American sequence to the best of our knowledge, and the data showed that RCNV forms a new phylogenetic branch between orthopoxviruses and Yoka poxvirus. RCNV shared overall similarity in genome organization with orthopoxviruses, and the proteins in the central conserved region shared approximately 90 % amino acid identity with orthopoxviruses. RCNV proteins shared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…It was recently reported that RCNV Herman strain is less virulent and much safer than VACV in immunocompromised or pregnant mouse models [ 54 ]. Although the wild type Herman strain was highly attenuated, deletion of TK gene attenuated it further [ 29 ], as is the case in VACV [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently reported that RCNV Herman strain is less virulent and much safer than VACV in immunocompromised or pregnant mouse models [ 54 ]. Although the wild type Herman strain was highly attenuated, deletion of TK gene attenuated it further [ 29 ], as is the case in VACV [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Raccoonpox virus (RCNV) is a member of the Orthopoxvirus genus and is closely related to the Vaccinia and Cowpox viruses [ 29 ]. RCNV was first isolated in 1961 from a naturally occurring infection from the respiratory tract of raccoons [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In case of MVA, this will require knowledge of the occurrence, distribution and characteristics of naturally circulating OPVs in locations and ecosystems in which recombinant MVA vaccines are to be deployed, especially for the vaccination of domesticated animals and wildlife. With the exception of Germany [ 112 , 113 , 114 , 115 , 116 ], United Kingdom [ 115 , 117 , 118 ], Fennoscandia [ 119 , 120 , 121 , 122 , 123 , 124 ], USA [ 125 , 126 , 127 , 128 ], Brazil [ 129 , 130 , 131 , 132 ] and India [ 133 , 134 , 135 ], data on the occurrence and characteristics of wild-type OPVs in remaining regions of the globe are limited or non-existent. MVA-vectored vaccines against malaria [ 136 , 137 ], HIV/AIDS [ 138 ], tuberculosis [ 68 ], Middle East respiratory syndrome coronavirus (MERS-CoV) [ 83 ], Ebola [ 73 ] and several other human and animal diseases [ 26 , 86 ] are in trials in Africa, Asia and Middle East, but knowledge of the characteristics and reservoir animal species for wild-type OPVs in these regions are largely non-existent.…”
Section: Knowledge Gaps and Omitted Researchmentioning
confidence: 99%
“…Several poxviruses are used as recombinant vectors to develop vaccines for a wide range of infectious diseases including bacterial, viral and parasitic pathogens, as well as for cancer therapies, and several are approved or currently in clinical trials [ 19 – 26 ]. The only HIV vaccine with demonstrated efficacy in humans to date employs an avian poxvirus vector, and it entered NIH-sponsored Phase 2b/3 trials in 2016 [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccinia virus is the most commonly used poxvirus vaccine vector; however, its use is limited by its potential virulence, especially in immunocompromised hosts [ 19 , 21 , 29 , 30 ]. Raccoonpox virus provides a safer vector compared to vaccinia virus [ 19 , 21 , 26 , 30 ], and the Modified Vaccinia virus Ankara (MVA) strain is even more attenuated, because it cannot replicate in most mammalian cells [ 31 ]. However MVA immunogenicity has been limiting, requiring high doses and boost vaccinations [ 28 , 31 – 38 ].…”
Section: Introductionmentioning
confidence: 99%